ENSURING PRIORITY FOR PUBLIC URBAN PASSENGER TRANSPORT ON URBAN STREETS AND ROAD NETWORK - E. V. Fomin; V. А. Zeer; E. S. Arefieva; N. V. Golub (Вестник СибАДИ, 2020)
Introduction. Recently, in large and medium-sized cities, the increase in traffic has been exacerbated by the growth of motorization and the lack of development of the road network. Increasing vehicle traffic to a critical level leads to overcapacity of the arteries and, as a consequence, increases the level of delay. Public urban mass passenger transport is one of the most vulnerable groups in this regard. In order to unload the city’s street network, it is necessary to reduce the level of road traffic. One of the effective measures to deal with this problem is to increase the attractiveness of urban mass passenger transport, i.e. to ensure an adequate level of service for passengers including high speed, which can be increased by giving priority to bus traffic. One of the prospects for prioritizing public urban transport is the development of individual lanes or streets for urban rolling stock only. Due to the lack of criteria for the allocation of separate lanes for urban rolling stock, they have begun to appear in the vast majority on the main streets of the city. There are a large number of urban highways used for the operation of only one public transport route with dedicated lanes on them. The need for such arrangements is questionable. It is therefore necessary to formulate the criteria that justify the need for a separate urban passenger lane on a given stretch of the city network. Thus, the purpose of this work is to identify patterns between traffic parameters and the parameters of the urban public passenger transport programme, which will determine the criteria for the need for a separate lane for urban land transport on each individual stretch of the network.Materials and methods. This article deals with the method of determining the need for a separate lane for public urban passenger transport on a given stretch of the road network. In order to improve the quality of the transport of passengers, a mathematical model has been developed, based on such indicators as the level of traffic delay and the share of passenger traffic in the total flow of participants. Results. The necessary conditions have been laid down the strict implementation of which determines the need to ensure the priority of urban mass public passenger transport on the section of the city’s street network under consideration.Discussion and conclusion. The dependencies obtained make it possible to identify the need to ensure the priority of urban transport.